Advances in the diagnosis, management, and treatment of neonates with laryngeal disorders. Issue 4 (August 2016) - Parkes, William J.; Propst, Evan J.
Summary: Neonatal airway obstruction due to laryngeal pathology may cause significant morbidity and even mortality. The most frequently occurring etiologies anatomically from superiorly to inferiorly include: laryngomalacia, saccular cyst, vocal fold paralysis, anterior glottic web, laryngeal atresia, laryngeal cleft, subglottic stenosis, and subglottic hemangioma. The pathophysiology, presentation, and treatment options for each of these entities are discussed with a focus on a multidisciplinary, evidence-based approach.